Transformation All the Way Down? European Union Integration and the Professional Socialization of Municipal Health Officials in Serbia. (18th October 2019) - Fagan, Adam; Sircar, Indraneel
Abstract: This article assesses whether different types of exposure to European Union (EU) modes of socialization are associated with differences in attitudes towards corruption, using Serbia as case study. Drawing on a survey of Serbian municipal health‐care officials, the article complements existing research on the impact of EU conditionality on attitudes at the national level, while also contributing to the understanding of the impact of domestic variables on Europeanization. Thus, the article's contribution to the wider literature is to interrogate the premise that in order to deliver substantive reform, attitudes and practices need to be changed via exposure to EU tutelage and processes. Our data suggest that the type of interaction that officials have with the EU and its processes matters. While those involved in EU harmonization activities were significantly more critical of clientelistic behaviour, there is no significant association between attitudes and doing daily EU‐related work or attending EU training.